Aphthous-like stomatitis of COVID-19 patients - Nuraldeen Maher Al-Khanati; Abanoub Riad; Mhd Eyad Sahloul; Miloslav Klugar (Universidade Estadual de Campinas, 2020)
The emerging evidence on oral symptoms that occur in conjunction with coronavirus disease (COVID-19) infection has triggered wide debates on the pathophysiology as well as the potential implications of these manifestations. Hereby, we aim to report according to the CARE guidelines the clinical characteristics of a COVID-19 patient with aphthous-like stomatitis from our clinic. We also performed a literature search in PubMed, Scopus, Google Scholar from inception until 6th of September 2020 with a combination of keywords (COVID-19 OR SARS-CoV-2) AND aphthous. On reviewing the emerging evidence of aphthous lesions in COVID-19, we have found that 14 cases were reported heretofore. Aphthous-like stomatitis as a characteristic condition of immuno-affected patients is a predictable and clinically relevant oral complication of COVID-19 patients. Further studies are warranted to establish its epidemiologic significance and to understand its pathophysiology in COVID-19 patients.